2018
DOI: 10.3102/0002831218772274
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Student Absenteeism in the Early Grades by Targeting Parental Beliefs

Abstract: Attendance in kindergarten and elementary school robustly predicts student outcomes. Despite this well-documented association, there is little experimental research on how to reduce absenteeism in the early grades. This paper presents results from a randomized field experiment in 10 school districts evaluating the impact of a low-cost, parent-focused intervention on student attendance in grades K–5. The intervention targeted commonly held parental misbeliefs undervaluing the importance of regular K–5 attendanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 41 publications
5
71
0
1
Order By: Relevance
“…Results indicated that the post test performance of the Experimental Group was significantly better than pretest performance of Experimental Group on students' attendance. These results support and extend previous studies about the effectiveness of technology in reducing absenteeism at schools e.g., (18,28,29) . Further, this intervention was different from that of (28) as it targeted at-risk students of different education level (Middle School) and used technology differently (for calling).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results indicated that the post test performance of the Experimental Group was significantly better than pretest performance of Experimental Group on students' attendance. These results support and extend previous studies about the effectiveness of technology in reducing absenteeism at schools e.g., (18,28,29) . Further, this intervention was different from that of (28) as it targeted at-risk students of different education level (Middle School) and used technology differently (for calling).…”
Section: Discussionsupporting
confidence: 91%
“…These regular communications with families of the students make them understand the important role that regular attendance at school can play in the all-round success of the student (17) . A combination of home visits, regular communications with parents/guardians and their involvement can successfully reduce chronic absenteeism (18) . This two-way communication makes strong links between school, community, and parents (19) .…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the attribute (absences) number of school absences, it would be ideal if 98.19% could respond with <=25 times (originally 97.97% in the descriptive analytics); if 1.35% could respond with <=50 times (originally 1.27%); and if 0.46% could respond with >50 times (originally 0.76%). The results suggest that fewer number of school absences could contribute to the achievement of a high-level of performance in the final exam G3, which is congruent with the findings of Robinson, Lee, Dearing, and Rogers [41].…”
Section: Hypothetical Scenariosupporting
confidence: 86%
“…For example, behavioral nudges have had some success in the short term in boosting early childhood attendance. In a randomized experiment of 26,000 K-5 students, parents of students in the bottom 60% of attendance across 10 school districts received mailers that reported the number of days their children had been absent from school and offered general information about the importance of attendance in early grades (Robinson, Lee, Dearing, & Rogers, 2017). Students in families who received the attendance mailings were absent 0.53 fewer days over the course of the entire school year, on average, than students in households who did not receive them.…”
Section: Past Interventions To Improve Children's School Attendancementioning
confidence: 99%